Penggunaan Aplikasi Duolingo sebagai Media Pembelajaran Tambahan Bahasa Jepang Mahasiswa TPL Angkatan 58: The Use of The Duolinggo Application as Additional Learning Media for Japanese Language by TPL Students of The 58th Cohort - Aliya Raihana; Zulhilmi, Muhammad Indra; Khoerunnisa, Ratu Hasna Tsana; Cahyani, Salsabila Diba; Alen, Sheren; Fedrianingsih, Devi; Marwa, Muthiah Humaira; Lestari, Humannisa Rubina (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
This research aims to determine the effect between using the Duolingo application as an additional medium for learning Japanese and increasing Japanese language skills after using the Duolingo application for Software Engineering Technology (TPL) class 58 students. This research uses quantitative methods. Data was collected through an online questionnaire to measure students' Japanese language skills with a total of 41 respondents. The research results show that there is a strong correlation of 0.634 and a significant value of 0.000 between the use of the Duolingo application and improving the Japanese language skills of TPL class 58 students.